The Price of Being International: Career Outcomes of International Master’s Recipients in U.S. Labor Market - Jiang, Xiushan; Kim, Dongbin (Journal of International Students, 2019)
This study sought to examine whether international master’s recipients (IMRs) who graduated from U.S. institutions have different early career outcomes in major and job match, annual earnings, and career satisfaction from their counterpart domestic master’s recipients (DMRs). By analyzing combined datasets of National Survey of Recent College Graduates, this study found that IMRs were 2 times more likely than DMRs to hold jobs that are related to their master’s degree. On the other hand, IMRs faced an 8% earnings disadvantage as compared with DMRs. There was no statistically significant difference in job satisfaction between IMRs and DMRs. The policy implications for postsecondary institutions and the U.S. were discussed.